When nonspecific histology can be a clue to the diagnosis: three cases of trigeminal trophic syndrome. (30th May 2014) - Cardoso, J. C.; Cokelaere, K.; Maertens, M.; Karim, N.; Jong, T. J.; Calonje, E.
Summary Trigeminal trophic syndrome (TTS) is a rare cause of facial ulceration, which is usually associated with damage to the trigeminal nerve pathway, either centrally or peripherally, the most common causes being cerebrovascular accidents and trigeminal nerve ablation procedures. We present three cases of TTS, emphasizing the histopathological features. All three patients presented with facial ulceration. Two patients had a single lesion, and the third had several ulcers. However, in all cases, there was involvement of the nasal ala, and the lesions were strictly unilateral. Histology consistently showed ulceration with signs of severe chronic trauma: scarring, lichenification and/or pseudoepitheliomatous hyperplasia. Diagnosis of TTS can be difficult, and requires close clinicopathological correlation. Histology is important in excluding the majority of possible conditions included in the differential diagnosis, mainly malignancy and infectious processes. Several treatments have been described, but TTS is frequently refractory to treatment.